PERAN PENDIDIKAN DALAM MEWUJUDKAN VISI INDONESIA EMAS 2045 - Rayimas Priti Aisyapuri; Refika Aulia Putri Wulandari; Ikmawati, Ikmawati; Zainuddin Untu (CV. ADIBA ASIHA AMIRA, 2025)
Education is the primary pillar of a nation's success. It plays a crucial role in advancing the Golden Indonesia Vision 2045. High-quality education enhances human resources, which, in turn, drives a country's progress. This study examines the role of education in supporting the Golden Indonesia Vision 2045, which serves as the foundation for national development. A descriptive qualitative method was employed through a literature review of journals, articles, and other credible sources. The findings reveal that Indonesia faces various challenges in improving education quality, requiring several solutions. These include enhancing teacher competence through technology-based training, strengthening curricula to align with industry demands, and increasing access to adequate educational facilities, particularly in remote areas. This study highlights the importance of adaptive and innovative educational policies to ensure equity and quality improvement in education. Consequently, Indonesian youth can develop into competent individuals ready to compete on a global scale, contributing to the realization of the Golden Indonesia Vision 2045.